2019
DOI: 10.1007/s11240-019-01615-5
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of callus-cultures of the Argentinean mistletoe, Ligaria cuneifolia (R. et P.) Tiegh (Loranthaceae) and screening of their polyphenolic content

Abstract: Ligaria cuneifolia (R. et P.) Tiegh (Loranthaceae), known as liga, muérdago criollo, or Argentinean mistletoe, is a hemiparasitic plant with a broad distribution in central and northern Argentina. Pharmacological studies showed that L. cuneifolia extracts have hypolipemic, antioxidant, antibacterial, and immunomodulatory effects. We have established callus cultures from embryo and haustoria fragments. The highest frequency of callus formation from embryos (85%) was obtained on White medium with 4% (w/v) sucros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…These compounds were reported as part of some mistletoes in previous investigations [ 22 , 23 ]. Lipid-lowering, antioxidant, antibacterial, and immunomodulatory effects are attributed to HCA, as in the case of L. cuneifolia known as “Creole mistletoe” or “Argentine mistletoe” [ 24 ]. Coffee is one of the primary sources of HCA.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds were reported as part of some mistletoes in previous investigations [ 22 , 23 ]. Lipid-lowering, antioxidant, antibacterial, and immunomodulatory effects are attributed to HCA, as in the case of L. cuneifolia known as “Creole mistletoe” or “Argentine mistletoe” [ 24 ]. Coffee is one of the primary sources of HCA.…”
Section: Discussionmentioning
confidence: 99%
“…The Loranthaceae family has been reported to have anti-inflammatory [11], antioxidant [12,13], antimalarial [14], antimicrobial, antiviral [15], and gastrointestinal properties [16]. Some studies performed in this family have reported the presence of glycosylated flavonoids [17] and cardiac glucosides [18]. In general, flavonoids and their glycosides have been shown to have a wide range of biological activity, including antioxidant [19,20], antimicrobial [21], vasodilatory [22], inhibitory enzymatic [23], anti-inflammatory [24], anti-tumor [25], and cytotoxic effects [26].…”
Section: Introductionmentioning
confidence: 99%
“…Plant material for in vitro cultures was collected, preserved, and shipped to the lab as described in Section 4.1.1 (histochemical analysis). Fresh and mature fruits were disinfected as previously described [19]. Then, approximately 70 embryos were transferred to glass tubes (one per tube) containing control White modified medium (CWM = White medium with 500 mg L −1 casein hydrolysate, 100 mg L −1 myo-inositol, B5 vitamins, and 4% (w/v) sucrose) supplemented with 2.50 µM NAA, 9.20 µM KIN, and 6.5 g L −1 of agar (micropropagation grade); pH was adjusted to 5.6-5.8.…”
Section: Histochemical Analysismentioning
confidence: 99%
“…There are only a few reports about the establishment of in vitro cultures from Loranthaceae species [17,18]. We have previously determined the conditions to initiate in vitro calli cultures from L. cuneifolia on White medium with 500 mg L −1 casein hydrolysate, 100 mg L −1 myo-inositol, B5 vitamins, 4% (w/v) sucrose, 2.50 µM NAA, and 9.20 µM KIN as plant growth regulators (PGRs) and a 16 h photoperiod [19]. The behavior of most plant cultures depends on the quality, intensity, and duration of the light period, since the activity of many of the enzymes involved in the biosynthetic pathways of metabolites is influenced by light [20].…”
Section: Introductionmentioning
confidence: 99%